2017
DOI: 10.1002/lary.26644
|View full text |Cite
|
Sign up to set email alerts
|

The anatomical evolution of the thyroid cartilage from childhood to adulthood: A computed tomography evaluation

Abstract: 4. Laryngoscope, 127:E354-E358, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 24 publications
5
15
0
2
Order By: Relevance
“…Some have noted the sexbased differences in the size of laryngeal structures that do not become marked until puberty. 2,15,16 It is thought that the relatively larger size of male laryngeal structures could make males less likely than females to experience laryngeal obstruction. 2 The mean age of our patients at diagnosis was 15.37 years, which does imply that a number of patients had already begun to experience or had completed puberty.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Some have noted the sexbased differences in the size of laryngeal structures that do not become marked until puberty. 2,15,16 It is thought that the relatively larger size of male laryngeal structures could make males less likely than females to experience laryngeal obstruction. 2 The mean age of our patients at diagnosis was 15.37 years, which does imply that a number of patients had already begun to experience or had completed puberty.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…We found that V1, V2, and V3 all increased with age. This may be due to the development and calcification of thyroid cartilage [ 12 , 13 ]. However, it is curious that a higher BMI was correlated to an increase in D1, D2 and D3 but not correlated to V1, V2, and V3.…”
Section: Discussionmentioning
confidence: 99%
“…Although the morphometry of the laryngeal skeleton significantly alters until puberty, these alterations does not demonstrate statistical differences between genders. However, male larynx enlarges significantly after puberty in comparison with female larynx (1,2). However, there is no report that evaluating gender differences of the normal glottal configuration in resting position.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of DM is increasing day by day. (1,2). The total number of diabetic patients is expected to be 439 million by 2030 (1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation